Water supply in the town of Aguascalientes. The aqueduct of Cedazo, 1731-1891 (Tzintzun, Revista de Estudios Históricos, 2016)
his paper presents an approach to the construction history of “saca de agua”or the aqueduct of Cedazo, initiated by the mayor Matías de la Mota in 1731 ata great cost. he discussion starts with a description of how it was founded asa water supply system in the town of Aguascalientes. he works were suspendedat the middle of the 18th century and started again as late as in 1827, duringthe period of the irst federal republic. In 1891, the aqueduct underwentgeneral refurbishment. he present paper describes the diferent stages of itsconstruction, pointing out the diiculties which emerged in each of them. Itis essential to highlight the importance of this work and the way it resultedin a qualitative improvement of the city’s water supply. he aqueduct’s qanatcharacter is also discussed in the article and therefore also its connection tothe ancient building tradition coming from the Near East, which was introducedin America by the Spanish conquerors and colonizers from the 16thcentury onwards. he core of this paper is based on original documentationfrom archives and is a contribution to the studies on environmental history,in particular on water supply and use.
Keywords: water; aqueducts; qanat’s; urban water supply; city of Aguascalientes